Policy-related transaction costs of agricultural policies in Finland - Ollikainen, Markku; Lankoski, Jussi; Nuutinen, Sami (MTT Agrifood Research Finland, 2008)
This paper assesses policy-related transaction costs (PRTC) associated with the main agricultural and agri-environmental policy instruments in Finland. We find that area-based income support measures entail low transaction costs as expressed in percent of payments, not only in Finland but also in other European countries. Moreover, transaction costs in the Finnish agri-environmental programme are surprisingly low. Within the agri-environmental programme, transaction costs increase with more targeted and differentiated agri-environmental measures. For the basic mandatory measures, these costs are even lower than the transaction costs for the area-based income support measures. What regards the most differentiated policy measures such as conservation of special biotopes or establishment of riparian buffer zones, transaction costs increase considerably. Combining these findings with the actual targets of the Finnish agricultural policies provides indirect evidence about the impacts of policy instruments and the efficiency of administration in implementing the instruments. For area-based income support measures, the Finnish administration seems to work very efficiently. For water protection targets, enforcement and division of labour within the administration seem to be insufficient.
Keywords: Ma; transaction costs; agricultural policies; targeting; efficiency of administration